Broadband acoustic pseudospin topological states based on the reverse spin-orbit coupling in generalized insulators - Liu, Chongrui; Lu, Yibing; He, Zhenxin; Guan, Wenliang; Huang, Zhen (Frontiers in Materials, 2024)
Acoustic topological insulators have the excellent characteristic of the pseudospin-dependent one-way transmission of sound edge states immune to backscattering. We realize the broadband acoustic pseudospin topological edge states with subwavelength generalized topological insulators, which is achieved by reverse pseudospin-orbit coupling. The subwavelength band and broadband nontrivial bandgap can be achieved by adjusting the topological structure of the scatterers and introducing resonators. The results demonstrate that the resonator can significantly reduce the frequencies of p-states and d-states by introducing resonance scattering; the scattering size and rotation angles change the frequencies of p-states and d-states in opposite directions by adjusting the distribution of the sound field. Then, we experimentally realize the pseudospin-dependent one-way transmission of sound edge states along the interface separating phononic crystals with distinct topological phases. Our research provides a systematic scheme for the design of acoustic topological insulators with versatile applications.